Pengaruh Profesionalisme dan Soft Skill terhadap Kinerja Pegawai dengan Motivasi Sebagai Variabel Intervening pada Pengadilan Negeri Jambi - Ahadi Ahadi; Arna Suryani; Sudirman Sudirman (Universitas Batanghari, 2023)
The purpose of this study is to obtain an overview of professionalism, soft skills, motivation, and employee performance at the Jambi District Court; and to determine the simultaneous and partial effect of professionalism and soft skills on employee motivation and performance; and to analyze the effect of motivation on employee performance. To answer the purpose of this research, this research is supported by theoretical studies related to research variables, namely professionalism, soft skills, motivation, and employee performance. In addition, the author is also looking for relevant previous research in the form of articles/journals to support this research. The population in this study is Civil Servants at the Jambi District Court which amounts to 70 employees with conditions in 2023. The data analysis technique used in this study is through path analysis followed by hypothesis testing through F test (Simultaneous) and t test (Partial). From the path analysis testing carried out, it was found that professionalism and soft skills have an influence on employee motivation and performance directly and indirectly simultaneously and partially. This explains the better the professionalism and soft skills possessed by employees, the better the motivation possessed by employees in carrying out their main duties and functions in improving their performance in the organization. This study concluded the professionalism, soft skills, motivation and performance of employees at the Jambi District Court in good and high condition. In addition, professionalism and soft skills simultaneously and partially have a positive and significant influence on employee motivation and performance at the Jambi District Court. Similarly, motivation has a positive and significant influence on employee performance.